Efektivitas Pembelajaran Kolaboratif pada Mata Kuliah Pembelajaran Matematika Berbasis Informatika - Ratih Handayani (Eksponen, 2019)
This research was investigated about the effectiveness of colaborative learning on Mathematics based Informatics which aimed at probing whether the use of Colaborative Learning in Mathematic Departement of University of Muhammadiyah Kotabumi is effective to be used on Mathematics based Informatics subject. The method used was decriptive quaitative. The colaborative learning was implied on the lesson plan design and during the learning process in 8 meetings consisting of 16 students as the research sample. Based on the research result, it was found that the use of colaborative learning is effective to be used on Mathematics based informatics subject.